Methodology, assessment and application of biotope mapping for urban parks in China: A case study on Riverside Park, Yichang - Zhao, Cong-cong; Yang, Yu-Qi; Hu, Yuan-Dong (Frontiers in Environmental Science, 2022)
China, like many other countries in the world, has declining biodiversity caused by urbanization. Urban parks are a patchwork of distinct biotopes and have significant conservation value for biodiversity. Biotope mapping is an essential tool for urban biodiversity conservation, ecological spatial planning and ecosystem management, however there are few studies on it in China. This study explores a practical scheme of biotope classification, assessment and application for urban parks. We updated a classification scheme which integrated vegetation structure to make it clearer and more appropriate for urban parks in factor selection and grade. To identify problems in the biotope, the assessment tool assessed biotope fragmentation and spontaneous vegetation diversity. The number of patches (NP), mean patch size (MPS) and fragmentation index (FI) were used to measure biotope fragmentation, and for species level we used the richness index and the Jaccard index. These methods were applied to Riverside Park, Yichang as a case study site to verify the applicability and explore methods for biodiversity conservation and restoration based on biotope mapping. The results show that this classification scheme has the potential to become a standard system for urban parks in China, according to the advantages of recognition of human activities and other species, wide applicability and easy learning. It is also shows that the evaluation method integrating fragmentation and diversity is feasible and reliable to identify the problems of biotope types, and practical strategies are developed according to the assessment results. Our findings provide guidance and reference for professionals on a new method to take urban biodiversity conservation and restoration from research to practice.